Potassium requirement for leaf biomass yield and K nutrition of stevia - Maniruzzaman, Md; Chowdhury, Tanzin; Rahman, Md Arifur; Chowdhury, Md Akhter Hossain (Fundamental and Applied Agriculture, 2017)
Potassium (K) is an essential plant nutrient affecting most of the biochemical and physiological processes. It is classified as a macronutrient due to large quantities being taken up by plants during their life cycle. With the aim of establishing a scientific basis of K fertilization on the growth, leaf production, minimum K requirement and critical leaf K concentration of stevia, a pot experiment was carried out in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University. Six levels of K viz. 0 (K0), 50 (K50), 100 (K100), 150 (K150), 200 (K200) and 250 (K250) kg ha-1 were used in acid and non- calcareous soils. Plants were harvested at 60 days after planting (DAP). Results showed that K application significantly influenced the growth attributes, leaf yield and other parameters. Highest values of most of the parameters were obtained at 200 kg K ha-1. Dry weight of stevia leaves at harvest was increased from 0.77-7.41g and 0.99-7.74g Pot-1 in acid and non-calcareous soils, respectively over control. Potassium content was directly proportional with the increased levels of K though uptake did not follow the same trend. Leaf critical K content was estimated to be ca 1.75 and 1.71% in the plants grown in acid and non-calcareous soils, respectively. The minimum K requirement for maximum leaf biomass production (80%) of stevia was also estimated to be ca 220 and 199 kg ha-1 grown in acid and non-calcareous soils, respectively. This study would contribute to improve K fertilization of stevia in various types of soil.